Fear of cancer progression and the quality of sexual life of female cancer patients in Romania - Kállay, Éva; Müller-Fabian, Andrea; Dégi, Csaba László (Frontiers in Public Health, 2024)
Introduction As cancer survival rates increase, it has become crucial to pay attention to the long-term quality of life of survivors, including sexual functioning. The quality of sexual life and fear of cancer progression are often unmet needs, significantly impacting cancer patients’ overall quality of life. In this study, we investigate these factors in Romanian female cancer patients and highlight their relationship with mental health and demographic variables. Methods This study included 242 Romanian female cancer patients who completed questionnaires assessing sexual functioning (EORTC QLQ-SHQ22), fear of cancer progression (FoP-Q), depression (PHQ-9), and anxiety (GAD-7). We examined these relationships using descriptive, exploratory, and regression analyses. Results Around 50% of patients reported impairments in sexual satisfaction and pain during sex. Lower sexual satisfaction increased sexual dysfunction, and heightened fear of cancer progression (FCP) were associated with depression, anxiety, younger age, lower education, rural residence, and unmarried status. Discussion This study reveals a complex interplay between sexual health, fear of cancer progression, and psychological well-being among female cancer survivors in Romania. Addressing sexual concerns, providing psychoeducation, promoting coping with the fear of progression, and utilizing interdisciplinary interventions are essential to improving these patients’ overall quality of life. These findings underscore the need for integrated care approaches that consider both physical and psychological dimensions of cancer survivorship.